The use of interactive technologies in studying modern russian female poetry in polylingual gymnasium - Gaynutdinova, Alina R. (2018)
In modern pedagogical science, interactive forms and methods of teaching are actively developed based on activity and dialogue forms of cognition, which allows organizing the education of students in gymnasiums, based on substantive and practical activities and interpersonal interaction. In literature and extracurricular activities a leading role of the traditional forms of organizing the activities play teachers and senior students. Lessons, lectures, seminars, solitary work of students, along with them interactive forms of teaching are widely introduced: role-playing game (lesson, concert, poetic theatre, dramatization poems of modern Russian poets,). Mini-conferences dedicated to the life and work of modern Russian poets. Solving problem situations (case studies) in the class of extracurricular reading "Modern Russian Female Poetry: Traditions and Innovation" (students create and publicly defend creative projects: they compose collections of poems, almanacs or bookreuters about modern Russian female poetry, write introductory articles and comments). In determining the characteristics of modern Russian female poetry, students are helped by methods of "brainstorming", discussion or debate, which enable them to discuss problems dynamically and publicly defend their position on the issue under discussion. The specifics of the teaching of Russian literature in the polylingual gymnasium suppose a comparative analysis of the works of modern Russian poets with the poems of poets of other nations (English, Tatar, etc.).